Sociology's unspoken weakness: Bringing epistemology back in. (December 2017) - Stones, Rob
Following the sustained criticism of positivism and empiricism in the social sciences through the 1960s and 1970s, social theory turned its attention resolutely towards ontology. This 'ontological turn' has provided sociology with an enviably rich and diverse palette of understandings emerging from a variety of theoretical traditions. This development has been accompanied, however, by a failure to construct a parallel epistemology with which to translate the variety, fullness and nuance of ontological concepts into strong and defensible empirical accounts. The article signals the complex nature of the consequent challenge and presents the components of a new epistemological framework designed to enable the social sciences to respond to it. Grounded theory is taken as an example of how an influential prior approach attuned to the role of concepts in making sense of empirical data could be constructively integrated into the new epistemology while being greatly strengthened by it. The article concludes with a critical discussion of John Law's After Method . Closely associated with Actor Network Theory (ANT), Law offers a 'hard case' against which to pitch my argument. This is because he holds that the subjective, contingent and 'assembled' character of knowledge renders both undesirable and impossible the project of epistemological rigour I present as both possible and essential.